Indacaterol/glycopyrronium versus tiotropium or glycopyrronium in long‐acting bronchodilator‐naïve COPD patients: A pooled analysis. Issue 4 (24th July 2019) - Muro, Shigeo; Yoshisue, Hajime; Kostikas, Konstantinos; Olsson, Petter; Gupta, Pritam; Wedzicha, Jadwiga A.
ABSTRACT: Background and objective: Indacaterol/glycopyrronium (IND/GLY) 110/50 μg once daily (q.d.) has demonstrated greater improvements in lung function, patient‐reported outcomes and lower exacerbation rates versus mono long‐acting muscarinic antagonists (LAMA) in chronic obstructive pulmonary disease (COPD) patients. However, data are limited on initial treatment with IND/GLY 110/50 μg q.d. versus mono LAMA in COPD patients, not previously on maintenance treatment with long‐acting bronchodilators (LABD). Methods: A pooled analysis of ARISE, SHINE and SPARK trials was conducted to evaluate the efficacy of IND/GLY 110/50 μg q.d. versus open‐label (OL) tiotropium (TIO) 18 μg q.d. and GLY 50 μg q.d. in COPD patients, not on maintenance treatment with LABD at study entry (LABD‐naïve). Efficacy was assessed after 24/26 weeks of treatment. Results: In total, 998 LABD‐naïve patients were included (IND/GLY: 353; OL TIO: 328; GLY: 317). Patients treated with IND/GLY 110/50 μg q.d. experienced greater improvements in trough forced expiratory volume in 1 s (FEV1 ) versus OL TIO 18 μg q.d. (least squares mean treatment difference (Δ): 0.086 L) and GLY 50 μg q.d. (Δ: 0.080 L) after 24/26 weeks. Improvements in electronic diary (eDiary) symptom scores, transition dyspnoea index (TDI) focal score, St George's Respiratory Questionnaire (SGRQ) total score and rescue medication use were also greater with IND/GLY versus OL TIO and GLY. Greater proportion of patients achieved minimal clinically important difference in trough FEV1, TDI and SGRQ with IND/GLY versus OL TIO and GLY. Conclusion: LABD‐naïve patients treated with IND/GLY 110/50 μg q.d. achieved improvements in lung function, daily symptoms, dyspnoea, health‐related quality of life and rescue medication use versus those who received single LAMA. Abstract : Data are limited on initial treatment with indacaterol/glycopyrronium (IND/GLY) versus mono long‐acting muscarinic antagonist (LAMA) in long‐acting bronchodilator (LABD)‐naïve chronic obstructive pulmonary disease (COPD) patients. This pooled analysis of ARISE, SHINE and SPARK trials demonstrated improvements with IND/GLY in lung function, daily symptoms, dyspnoea, health‐related quality of life and rescue medication use versus tiotropium or GLY in LABD‐naïve COPD patients. See related Editorial